A Contrastive Study of Superlative Comparison Schemas in Persian and English: A Cognitive-Typological Account - Ava Imani (زبان پژوهی, 2023)
Comparison is a fundamental aspect of human cognition that is expressed in various ways across languages. However, it cannot be solely described by individual words or morphemes; rather, its existence depends on underlying schematic structures. Heine (1997) notes that the domain of comparison encompasses different conceptual and linguistic forms, with the "superior comparative" serving as a prototypical example in languages worldwide. It is worth noting that both "superior comparative" and "superlative" constructions share common underlying structures. This study hypothesizes that Persian exhibits a greater variety of language-specific superlative constructions compared to English, attributed to typological features such as the "Ezafe construction," "free word order," as well as other morpho-syntactic elements including constructional idioms, specific lexical items, and phrasal/complex predicates unique to Persian.This study aims to address the following questions: 1) What schemas and morpho-syntactic mechanisms do Persian and English employ to express the superlative comparison notion? 2) Do all constructive components of superlative comparison in Persian and English require obligatory or optional formal expression? 3) To what extent can Stassen's typological classification (1985) and Heine's cognitive approach (1997) explain the superlative comparative constructions in these two languages? 4) How similar or different are the dedicated grammaticalized constructions employed by Persian and English to express the superlative comparison notion?